2016
DOI: 10.1155/2016/3246946
|View full text |Cite
|
Sign up to set email alerts
|

A Network Pharmacology Approach to Uncover the Pharmacological Mechanism of XuanHuSuo Powder on Osteoarthritis

Abstract: As the most familiar type of arthritis and a chronic illness of the joints, Osteoarthritis (OA) affects a great number of people on the global scale. XuanHuSuo powder (XHSP), a conventional herbal formula from China, has been extensively applied in OA treatment. Nonetheless, its pharmacological mechanism has not been completely expounded. In this research, a network pharmacology approach has been chosen to study the pharmacological mechanism of XHSP on OA, and the pharmacology networks were established based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 76 publications
0
38
0
Order By: Relevance
“…The causes of osteoarthritis are complex, and the pathogenesis related to this disease is not well understood (4). Osteoarthritis is divided into primary and secondary osteoarthritis according to the presence of local and systemic risk factors (5). Osteoarthritis is frequently diagnosed as rheumatoid arthritis or ankylosing spondylitis in clinical differential diagnosis (1,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of osteoarthritis are complex, and the pathogenesis related to this disease is not well understood (4). Osteoarthritis is divided into primary and secondary osteoarthritis according to the presence of local and systemic risk factors (5). Osteoarthritis is frequently diagnosed as rheumatoid arthritis or ankylosing spondylitis in clinical differential diagnosis (1,6).…”
Section: Introductionmentioning
confidence: 99%
“…PRP also possesses multifunctional outcomes for the treatment of osteoarthritis, including osteonecrosis of the femoral head, cartilage injury and rheumatoid arthritis (9). Previous research has suggested that PRP exhibits benefits for injurious articular cartilage repair through the removal of harmful inflammation factors in patients with joint diseases (5). It has previously been reported that PRP was beneficial for rheumatoid arthritis without side effects through inhibition of inflammatory factor levels in synovial fluid (10).…”
Section: Introductionmentioning
confidence: 99%
“…As TCMs are increasingly being used to treat OA (39), scientists have suggested that certain TCMs, particularly those used in combination formulas, may produce therapeutic effects in a synergistic manner. For example, XuanHuSuo powder (XHSP), a conventional herbal formulation developed in China, has been extensively used in OA treatment (40). XHSP has shown reasonable efficacy as an anti-apoptotic and anti-inflammatory agent when applied following stimulation with a cytokine (IL-1β) or estrogen (40).…”
Section: Discussionmentioning
confidence: 99%
“…For example, XuanHuSuo powder (XHSP), a conventional herbal formulation developed in China, has been extensively used in OA treatment (40). XHSP has shown reasonable efficacy as an anti-apoptotic and anti-inflammatory agent when applied following stimulation with a cytokine (IL-1β) or estrogen (40). As an active component of various Chinese herbs, berberine chloride has been demonstrated to benefit matrix synthesis and cell survival in IL-1β-stimulated chondrocytes, and displays great therapeutic potential as a promoter of cartilage repair in rat OA models (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies are still applying the traditional research idea, “one-drug-one target-one-illness,” which ignores the multitarget and multicomponent characteristic of TCM recipes. Inspired by Tang et al's research [77], we decided to solve this problem by network pharmacology. In this study, a number of network-based computational methods and algorithm-based approaches to predict targets and construct networks are combined to illuminate the molecular synergy of XYP for infertility.…”
Section: Discussionmentioning
confidence: 99%